The beginning of everything - Schneider, Robyn (New York : Katherine Tegen Books, 2013)
"Star athelete and prom king Ezra Faulkner's life is irreparably transformed by a tragic accident and the arrival of eccentric new girl Cassidy Thorpe."--
Keywords: People with disabilities -- Fiction; Interpersonal relations -- Fiction; High schools -- Fiction; Schools -- Fiction; Debates and debating -- Fiction; Family life -- California -- Fiction; California -- Fiction